1977
DOI: 10.1071/ph770241
|View full text |Cite
|
Sign up to set email alerts
|

The Molonglo Deep Sky Survey of Radio Sources. III. Source Counts

Abstract: Aust, J. Phys., 1977,30, 241-9 Number-flux density counts of radio sources are given for the first two deep surveys made with the Molonglo Mills Cross at 408 MHz, extending to lower limits of 84 and 88 mJy. Practical techniques are developed for the calculation of corrections to the counts when confusion errors are significant. The resulting corrections due to noise, confusion and other effects are given. Counts are also given for the MC2 and MC3 catalogues in the range 2-10 Jy to reduce the statistical unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Reference codes. be82: Benn et al (1982); gr88: Grueff (1988); ro77: Robertson (1977). Table 8 Euclidean normalized differential 15.2 GHz source counts from the 9C survey (Waldram et al 2003(Waldram et al , 2009…”
Section: Discussionmentioning
confidence: 99%
“…Reference codes. be82: Benn et al (1982); gr88: Grueff (1988); ro77: Robertson (1977). Table 8 Euclidean normalized differential 15.2 GHz source counts from the 9C survey (Waldram et al 2003(Waldram et al , 2009…”
Section: Discussionmentioning
confidence: 99%
“…where the differential slope of the distribution of number of sources as a function of flux density becomes markedly less negative than -2.5 (Robertson 1977c). The increased proportion of flat spectrum sources at low flux density is consistent with the fact that source counts at higher frequencies (Wall and Cooke 1975) fall less rapidly below the "Euclidean" slope than at 408 MHz (Robertson 1977c). The present result would seem to indicate that the counts of steep spectrum sources at 408 MHz are falling more steeply below the "Euclidean" slope than previously recognized.…”
Section: Discussionmentioning
confidence: 91%
“…The changes occur in the region where the radio source counts begin to fall sharply below the so-called "Euclidean" slope i.e. where the differential slope of the distribution of number of sources as a function of flux density becomes markedly less negative than -2.5 (Robertson 1977c). The increased proportion of flat spectrum sources at low flux density is consistent with the fact that source counts at higher frequencies (Wall and Cooke 1975) fall less rapidly below the "Euclidean" slope than at 408 MHz (Robertson 1977c).…”
Section: Discussionmentioning
confidence: 99%
“…Robertson (1976c), in comparing his deep surveys with the Cambridge 5C surveys, found that the Molonglo catalogues contain more sources than the Cambridge, above equivalent levels, by a factor of 1.29. The formal significance is about 1% but, in view of the increased probability of calibration discordances between two quite different catalogues, this indication of anisotropy is very weak.…”
Section: Mc1mentioning
confidence: 99%